Research Hesitancy in the Academe: A Multi-University Study in the Philippines - Durante, Cherry Ann G.; Reynoso, Lino C.; Lorenzo, Lorenzo C.; Nunez, Norma G.; Calixtro Jr., Rufo; Juan, Estrella San; Frani, Jeeno Jay (Future Science / FSH-PH Publications, 2023)
ABSTRACT Cultivating a culture of research in the academe is one of the goals of every institution of higher education in the Philippines. Despite of this, there exists a hesitation among faculty and non-teaching staff in engaging in research and publication. This study explored the reasons behind the decrease of research productivity in the academe in different higher education institutions in the Philippines. Sixteen faculty members from different disciplines were included in the study and were interviewed from November to December 2022. Employing a descriptive phenomenological research design, results showed that the causes of research hesitancy were summarized into four domains, namely: individual, institutional, scientific and professional domains. Under the individual domain, the themes of lack of confidence, lack of motivation, lack of time and lack of interest were identified. The institutional domain enumerated lack of research training, equipment, lack of research programs and funding deficiency. The scientific domain contained themes like lack of knowledge, skill and expertise in conduct of research and writing publishable papers. The professional domain identified themes that revolve around lack of access, lack mentors and lack of collaboration between faculty members. Based on the results of the study, all of the participants expressed the lack of funding support, which included tedious methods of acquiring such funding from the institution and other stakeholders as the primary cause of their hesitancy. Furthermore, participants expressed that individual factors that cause research hesitancy are most difficult to overcome as it pertains to past negative experiences, which led to the reluctance to be trained or to engage in research. The lack of a research culture within the institution was also linked to the absence of a clear research agenda and program, and capacity-building programs geared towards faculty researcher development.